MOF compound adsorbent based on foamy copper as well as preparation method and application of MOF compound adsorbent
The hydrothermal method of using foam copper base material and copper hydroxide nanowire array and hexahydroxy tribene in MOFs materials was prepared in a hydrothermal method to form Cu3 (HHTP) 2 nanorods, which solved the problem of poor thermal conductivity and lack of photothermal conversion of MOFs materials. , efficient water molecule adsorption and solar-driven autonomous desorption are achieved, reducing energy consumption.
Patent Information
- Application Number
- CN202411362059.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
AI Technical Summary
The existing MOFs materials with water molecule absorption and desorption function have poor thermal conductivity and do not have photothermal conversion performance, resulting in low desorption efficiency and high energy consumption.
Using foamed copper with smooth surface, connecting channels and excellent heat transfer properties as the base material, the copper hydroxide nanowire array was grown by in-situ etching in strong alkali solution, and with 2,3,6,7,10,11-6 Hydroxytriene is converted into Cu3 (HHTP) 2 nanorods by hydrothermal method, forming a MOF foam composite adsorbent with a three-dimensional porous structure, and has excellent thermal conductivity and photothermal conversion capabilities.
The adsorption and desorption efficiency of water molecules is improved, and the independent photothermal desorption under sunlight is achieved, energy consumption is reduced, and the photothermal effect during adsorption saturation is significantly improved.
Smart Images

Figure CN119236892A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adsorption-type air water extraction materials, and in particular to a MOF composite adsorbent based on foam copper, and a preparation method and application thereof. Background Art
[0002] The increasingly severe water shortage problem around the world has attracted great attention from all walks of life. In the past few decades, people have developed many freshwater acquisition technologies, including seawater desalination and wastewater purification. These traditional methods have alleviated the shortage of water resources to a certain extent, but they are limited by many factors such as economic cost, geographical location and environmental conditions. The water content in the atmosphere is one-eighth of all rivers, lakes and reservoirs on the earth's surface, which is relatively abundant and is a natural freshwater reservoir. Therefore, more and more scientific researchers are investing in the research of air water extraction technology.
[0003] Air water extraction technology mainly includes condensation water extraction based on compression refrigeration or radiation refrigeration, fog capture under high humidity, dew collection, and air water extraction technology based on adsorption. Among them, the air water extraction technology based on adsorption is a method of using adsorbent materials to spontaneously capture water vapor in the ambient air and store it in the form of adsorbed water, and then release the wet hot steam under heat drive and condense it to obtain fresh water. Considering that the ambient humidity in general areas varies greatly throughout the year, adsorption air water extraction has more practical advantages for arid areas that require a stable water supply throughout the year.
[0004] In the field of adsorption-based air water extraction technology, the adsorption and desorption performance of water molecules is the core property of adsorbent materials. At present, the developed adsorbent materials are mainly divided into traditional adsorbents, liquid adsorbents, polymer adsorbents and adsorbents based on Metal-Organic Frameworks (MOFs) materials. Among them, traditional adsorbents have low adsorption capacity, liquid adsorbents are prone to deliquesce and corrode equipment during adsorption and desorption, and polymer adsorbents have slow adsorption and desorption rates. MOFs have high porosity, large specific surface area, and structure and function that can be regulated in a direction, and have received widespread attention in the past decade. As a water molecule adsorbent, MOFs have the advantages of fast adsorption and desorption rates and a wide adsorption humidity range, and have very potential applications in the field of air water extraction.
[0005] However, current MOFs materials that have the function of adsorbing and desorbing water molecules have the following shortcomings: (1) MOF materials have poor thermal conductivity, which leads to uneven heat distribution inside and outside the material during thermal desorption, reducing the desorption efficiency; (2) MOF materials mostly exist in powder form and must be compacted before they can be used. The compaction process increases the mass transfer resistance of water molecules in the material and reduces the adsorption and desorption rates; (3) MOF materials do not have photothermal conversion properties. The heat required for the desorption process can only be provided by electric heating, which increases the energy consumption of the water extraction process. Summary of the invention
[0006] In view of this, the purpose of the present invention is to provide a MOF composite adsorbent based on copper foam and a preparation method and application thereof, so as to at least solve the problem that the existing MOFs materials with water molecule adsorption and desorption functions have poor thermal conductivity and lack of photothermal conversion performance.
[0007] The present invention solves the above technical problems by the following technical means:
[0008] In a first aspect, the present invention provides a method for preparing a MOF composite adsorbent based on copper foam, wherein the preparation method comprises immersing a copper hydroxide foam block in a HHTP solution, sealing the block and reacting the block at 68 to 75° C. for 2 to 4 hours, rinsing the obtained solid with deionized water, ethanol and acetone, and drying the solid in a vacuum environment at 70 to 80° C. to obtain a MOF composite adsorbent based on copper foam.
[0009] In combination with the first aspect, in some embodiments, the HHTP solution is configured as follows:
[0010] Add 2,3,6,7,10,11-hexahydroxytriphenylene into dimethylacetamide, disperse by ultrasonic wave, and prepare an organic solution;
[0011] The organic solution was mixed with deionized water in a volume ratio of 1:10 to obtain a HHTP solution.
[0012] In combination with the first aspect, in some embodiments, the concentration of 2,3,6,7,10,11-hexahydroxytriphenylene in the organic solution is 3.5-4 mmol / L.
[0013] In combination with the first aspect, in some embodiments, the amount of the copper hydroxide foam block and 2,3,6,7,10,11-hexahydroxytriphenylene is as follows: 0.015-0.025 mol 2,3,6,7,10,11-hexahydroxytriphenylene is soaked per cubic centimeter of the copper hydroxide foam block.
[0014] In combination with the first aspect, in some embodiments, the copper hydroxide foam block is prepared as follows:
[0015] The pretreated copper foam block is immersed in a mixed alkali aqueous solution, and allowed to stand at room temperature for 30 to 60 minutes until the surface of the copper foam block changes from orange to blue, and then taken out and repeatedly rinsed with deionized water and ethanol, and vacuum dried to obtain a copper hydroxide foam block; the mixed alkali aqueous solution contains sodium hydroxide and ammonium persulfate.
[0016] In combination with the first aspect, in some embodiments, the concentration of sodium hydroxide in the mixed alkaline solution is 1 mol / L, and the concentration of ammonium persulfate is 0.1 mol / L.
[0017] In combination with the first aspect, in some embodiments, 35 to 45 mL of the mixed alkali aqueous solution is used to soak each cubic centimeter of the foamed copper.
[0018] In combination with the first aspect, in some embodiments, the pretreatment of the foam copper block is as follows:
[0019] The foam copper with a purity of more than 99.9% is cut into cubes, soaked in 10% dilute sulfuric acid for 10 to 15 minutes, then soaked in ultrapure water for 20 to 30 minutes, soaked in acetone and ultrasonicated for 10 to 20 minutes, then ultrasonicated for 10 to 15 minutes, washed with deionized water, and dried.
[0020] In a second aspect, the present invention provides a MOF composite adsorbent based on copper foam, wherein the MOF composite adsorbent is prepared by the preparation method described in the first aspect.
[0021] In a third aspect, the present invention provides the use of the MOF composite adsorbent based on copper foam described in the second aspect in adsorption-type air water extraction.
[0022] In the preparation method of the MOF composite adsorbent based on copper foam of the present invention, a copper foam with a smooth surface, interconnected pores and excellent heat transfer performance is selected as a base material, and the copper foam is etched in situ in a strong alkaline solution to grow a copper hydroxide nanowire array, and then the copper hydroxide is converted into intertwined Cu3(HHTP)2 nanorods by a hydrothermal method with 2,3,6,7,10,11-hexahydroxytriphenylene, to obtain a MOF foam composite adsorbent material with a three-dimensional porous structure based on copper foam. The π-π transition of the ligand 2,3,6,7,10,11-hexahydroxytriphenylene in Cu3(HHTP)2 can absorb ultraviolet light and visible light, and then convert it into heat energy, so it has excellent photothermal conversion ability, and also has strong thermal conductivity and stability. When adsorption is saturated, photothermal autonomous desorption can be achieved under the irradiation of sunlight.
[0023] The Cu3(HHTP)2 foam material prepared by the present invention has a three-dimensional fluffy porous structure formed by interweaving Cu3(HHTP)2 nanowires on its surface. There are gaps between the entangled Cu3(HHTP)2 nanowires, which can effectively increase the contact area with the air and facilitate the transfer of water molecules. On the other hand, the multi-level channels formed by the Cu3(HHTP)2 nanoarray can enhance light absorption and thus improve the photothermal effect.
[0024] According to tests, the Cu3(HHTP)2 foam material of the present invention exhibits strong absorption capacity in the entire solar light band. In the wavelength range of 500-1900nm (visible light band and infrared band), its light absorption rate is higher than 80%, and can reach up to 99.5%. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is the PXRD pattern of the MOF composite adsorbent prepared in Example 2;
[0026] Figure 2 is the SEM image of the copper foam block, copper hydroxide foam block and Cu3(HHTP)2 foam material in Example 2;
[0027] Figure 3 is a graph showing the relationship between the mass of water vapor adsorbed per unit area of the Cu3(HHTP)2 foam material of Example 2 and time;
[0028] Figure 4 It is the saturated adsorption capacity diagram of Cu3(HHTP)2 foam material at different humidity;
[0029] Figure 5 is the absorbance test result of the Cu3(HHTP)2 foam material of Example 2;
[0030] Figure 6 It is the graph of the maximum temperature of the surface of Cu3(HHTP)2 foam material changing with time before and after illumination;
[0031] Figure 7 This is the thermal conductivity test calculation result diagram;
[0032] Figure 8 This is the desorption performance test result diagram of Cu3(HHTP)2 foam material;
[0033] Fig. 9 This is the adsorption-desorption cycle test result diagram of Cu3(HHTP)2 foam material;
[0034] Fig.10 This is the PXRD pattern of Cu3(HHTP)2 foam material after 15 cycles of adsorption and desorption. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The raw materials, equipment or instruments used, if no manufacturer is specified, are all conventional products that can be purchased on the market.
[0037] The MOF composite adsorbent based on copper foam of the present invention selects copper foam with a smooth surface, interconnected pores and excellent heat transfer performance as a base material, in-situ etching is performed on the copper foam in a strong alkaline solution to grow a copper hydroxide nanowire array, and then the copper hydroxide is converted into mutually intertwined Cu3(HHTP)2 nanorods by a hydrothermal method with 2,3,6,7,10,11-hexahydroxytriphenylene (2,3,6,7,10,11-hexahydroxytriphenylene, HHTP), thereby obtaining a MOF foam composite adsorbent material based on copper foam with a three-dimensional porous structure. The π-π transition of the ligand 2,3,6,7,10,11-hexahydroxytriphenylene in Cu3(HHTP)2 can absorb ultraviolet light and visible light, and then convert it into heat energy, so it has excellent photothermal conversion ability, and can achieve photothermal autonomous desorption under the irradiation of sunlight when adsorption is saturated.
[0038] For details, please refer to Examples 1-4:
[0039] Example 1
[0040] The preparation method of the MOF composite adsorbent based on copper foam in this embodiment is as follows:
[0041] (1) Preparation of copper hydroxide foam blocks
[0042] The foam copper with a thickness of 0.3 mm and a purity of 99.9% was cut into small cubes, and the cut foam copper cubes were immersed in 10% by mass dilute sulfuric acid for 10 minutes, then immersed in ultrapure water for 20 minutes, immersed in acetone and ultrasonicated for 10 minutes to remove surface oxides and other impurities, and then washed with deionized water and dried to complete the pretreatment of the foam copper blocks.
[0043] Sodium hydroxide and ammonium persulfate are added to deionized water to prepare a mixed alkali aqueous solution with a sodium hydroxide concentration of 1 mol / L and an ammonium persulfate concentration of 0.1 mol / L; 35 mL of the mixed alkali aqueous solution is used per cubic centimeter of copper foam, and the pretreated copper foam block is immersed in the mixed alkali aqueous solution and allowed to soak for 30 minutes at room temperature. During the soaking process, the transparent mixed alkali aqueous solution will gradually turn blue, and the orange surface of the copper foam will turn blue. Take it out and rinse it repeatedly with deionized water and ethanol to remove the alkali solution attached to the surface, and then put it into a vacuum drying oven for drying to obtain a blue copper hydroxide foam block.
[0044] (2) Preparation of MOF composite adsorbent
[0045] 2,3,6,7,10,11-Hexahydroxytriphenylene was added to dimethylacetamide, and ultrasonic dispersion was performed for 5 minutes to uniformly disperse HHTP to obtain an organic solution with a concentration of 3.5 mmol / L of 2,3,6,7,10,11-Hexahydroxytriphenylene. Then, deionized water 10 times the volume of the organic solution was added, and ultrasonic dispersion was continued for 10 minutes to obtain a HHTP solution.
[0046] The copper hydroxide foam block was immersed in the HHTP solution according to the amount of 0.015 mol 2,3,6,7,10,11-hexahydroxytriphenylene per cubic centimeter of the copper hydroxide foam block, and then sealed and placed at 68°C for reaction for 2 hours. The obtained solid was repeatedly rinsed with deionized water, ethanol and acetone, and dried in a vacuum environment at 70°C to obtain a copper foam-based Cu3(HHTP)2 foam material, that is, a copper foam-based MOF composite adsorbent.
[0047] Example 2
[0048] The preparation method of the MOF composite adsorbent based on copper foam in this embodiment is as follows:
[0049] (1) Preparation of copper hydroxide foam blocks
[0050] The foam copper with a thickness of 0.3 mm and a purity of 99.9% was cut into small cubes, and the cut foam copper cubes were soaked in 10% dilute sulfuric acid for 13 minutes, then soaked in ultrapure water for 25 minutes, soaked in acetone and ultrasonicated for 25 minutes to remove surface oxides and other impurities, and then washed with deionized water and dried to complete the pretreatment of the foam copper blocks.
[0051] Sodium hydroxide and ammonium persulfate are added to deionized water to prepare a mixed alkali aqueous solution with a sodium hydroxide concentration of 1 mol / L and an ammonium persulfate concentration of 0.1 mol / L; 40 mL of the mixed alkali aqueous solution is used per cubic centimeter of copper foam, and the pretreated copper foam block is immersed in the mixed alkali aqueous solution and allowed to soak for 40 minutes at room temperature. During the soaking process, the transparent mixed alkali aqueous solution will gradually turn blue, and the orange surface of the copper foam will turn blue. Take it out and rinse it repeatedly with deionized water and ethanol to remove the alkali solution attached to the surface, and then put it into a vacuum drying oven for drying to obtain a blue copper hydroxide foam block.
[0052] (2) Preparation of MOF composite adsorbent
[0053] 2,3,6,7,10,11-Hexahydroxytriphenylene was added to dimethylacetamide, and ultrasonic dispersion was performed for 5 minutes to uniformly disperse HHTP to obtain an organic solution with a concentration of 3.6 mmol / L of 2,3,6,7,10,11-hexahydroxytriphenylene. Then, deionized water 10 times the volume of the organic solution was added, and ultrasonic dispersion was continued for 10 minutes to obtain a HHTP solution.
[0054] The copper hydroxide foam block was immersed in the HHTP solution according to the amount of 0.02 mol 2,3,6,7,10,11-hexahydroxytriphenylene per cubic centimeter of the copper hydroxide foam block, and then sealed and placed at 70°C for reaction for 3 hours. The obtained solid was repeatedly rinsed with deionized water, ethanol and acetone, and then dried in a vacuum environment at 75°C to obtain a copper foam-based Cu3(HHTP)2 foam material, that is, a copper foam-based MOF composite adsorbent.
[0055] Example 3
[0056] The preparation method of the MOF composite adsorbent based on copper foam in this embodiment is as follows:
[0057] (1) Preparation of copper hydroxide foam blocks
[0058] The foam copper with a thickness of 0.3 mm and a purity of 99.9% was cut into small cubes, and the cut foam copper cubes were soaked in 10% dilute sulfuric acid for 15 minutes, then soaked in ultrapure water for 30 minutes, soaked in acetone and ultrasonicated for 20 minutes to remove surface oxides and other impurities, and then washed with deionized water and dried to complete the pretreatment of the foam copper blocks.
[0059] Sodium hydroxide and ammonium persulfate are added to deionized water to prepare a mixed alkali aqueous solution with a sodium hydroxide concentration of 1 mol / L and an ammonium persulfate concentration of 0.1 mol / L; 45 mL of the mixed alkali aqueous solution is used per cubic centimeter of copper foam, and the pretreated copper foam block is immersed in the mixed alkali aqueous solution and allowed to soak for 60 minutes at room temperature. During the soaking process, the transparent mixed alkali aqueous solution will gradually turn blue, and the orange surface of the copper foam will turn blue. Take it out and rinse it repeatedly with deionized water and ethanol to remove the alkali solution attached to the surface, and then put it into a vacuum drying oven for drying to obtain a blue copper hydroxide foam block.
[0060] (2) Preparation of MOF composite adsorbent
[0061] 2,3,6,7,10,11-Hexahydroxytriphenylene was added to dimethylacetamide, and ultrasonic dispersion was performed for 5 minutes to uniformly disperse HHTP to obtain an organic solution with a concentration of 4 mmol / L of 2,3,6,7,10,11-Hexahydroxytriphenylene. Then, deionized water 10 times the volume of the organic solution was added, and ultrasonic dispersion was continued for 10 minutes to obtain a HHTP solution.
[0062] The copper hydroxide foam block was immersed in the HHTP solution according to the amount of 0.025 mol 2,3,6,7,10,11-hexahydroxytriphenylene per cubic centimeter of the copper hydroxide foam block, and then sealed and placed at 75°C for reaction for 4 hours. The obtained solid was repeatedly rinsed with deionized water, ethanol and acetone, and then dried in a vacuum environment at 80°C to obtain a copper foam-based Cu3(HHTP)2 foam material, that is, a copper foam-based MOF composite adsorbent.
[0063] Example 4
[0064] The preparation method of the MOF composite adsorbent based on copper foam in this embodiment is as follows:
[0065] (1) Preparation of copper hydroxide foam blocks
[0066] The foam copper with a thickness of 0.3 mm and a purity of 99.9% was cut into small cubes, and the cut foam copper cubes were immersed in 10% by mass dilute sulfuric acid for 14 minutes, then immersed in ultrapure water for 20 minutes, immersed in acetone and ultrasonicated for 15 minutes to remove surface oxides and other impurities, and then washed with deionized water and dried to complete the pretreatment of the foam copper blocks.
[0067] Sodium hydroxide and ammonium persulfate are added to deionized water to prepare a mixed alkali aqueous solution with a sodium hydroxide concentration of 1 mol / L and an ammonium persulfate concentration of 0.1 mol / L; 40 mL of the mixed alkali aqueous solution is used per cubic centimeter of copper foam, and the pretreated copper foam block is immersed in the mixed alkali aqueous solution and allowed to soak for 40 minutes at room temperature. During the soaking process, the transparent mixed alkali aqueous solution will gradually turn blue, and the orange surface of the copper foam will turn blue. Take it out and rinse it repeatedly with deionized water and ethanol to remove the alkali solution attached to the surface, and then put it into a vacuum drying oven for drying to obtain a blue copper hydroxide foam block.
[0068] (2) Preparation of MOF composite adsorbent
[0069] 2,3,6,7,10,11-Hexahydroxytriphenylene was added to dimethylacetamide, and ultrasonic dispersion was performed for 5 minutes to uniformly disperse HHTP to obtain an organic solution with a concentration of 3.8 mmol / L of 2,3,6,7,10,11-hexahydroxytriphenylene. Then, deionized water 10 times the volume of the organic solution was added, and ultrasonic dispersion was continued for 10 minutes to obtain a HHTP solution.
[0070] The copper hydroxide foam block was immersed in the HHTP solution according to the amount of 0.02 mol 2,3,6,7,10,11-hexahydroxytriphenylene per cubic centimeter of the copper hydroxide foam block, and then sealed and placed at 70°C for reaction for 3 hours. The obtained solid was repeatedly rinsed with deionized water, ethanol and acetone, and then dried in a vacuum environment at 75°C to obtain a copper foam-based Cu3(HHTP)2 foam material, that is, a copper foam-based MOF composite adsorbent.
[0071] The MOF composite adsorbent prepared in Example 2 was used as a sample to perform the following tests:
[0072] (1) The X-ray diffraction (PXRD) data of the MOF composite adsorbent prepared in Example 2 were tested. The results are shown in Figure 1 . Figure 1 It can be seen that by comparing the simulated Cu3(HHTP)2 data, it is found that the position of the foam material peak is completely consistent with the simulated data, indicating that the preparation method of the present invention successfully grows Cu3(HHTP)2 on the surface of the foam copper.
[0073] (2) The copper foam block, copper hydroxide foam block and Cu3(HHTP)2 foam material in Example 2 were scanned by electron microscope. The scanning results are shown in Figure 2 .from Figure 2 It can be seen that the surface of the Cu3(HHTP)2 foam material is a three-dimensional fluffy porous structure formed by interweaving Cu3(HHTP)2 nanowires. There are gaps between the entangled Cu3(HHTP)2 nanowires. On the one hand, it can effectively increase the contact area with the air and facilitate the transfer of water molecules. On the other hand, the multi-level channels formed by the Cu3(HHTP)2 nanoarray can enhance light absorption and thus improve the photothermal effect.
[0074] (3) The Cu3(HHTP)2 foam material prepared in Example 2 was used as a sample to test its water absorption at different relative humidities. The water adsorption performance of the Cu3(HHTP)2 foam material was tested at room temperature (20±2°C). The foam material was placed in a constant temperature and humidity chamber, and the relative humidity was set to 15%, 20%, 30%, 40%, 50% and 60%, respectively. It was taken out and weighed every 5 minutes and recorded. The water adsorption per unit area m was calculated according to the following formula:A (gm –2 ):
[0075]
[0076] Wherein, ms is the mass of Cu3(HHTP)2 foam material when it reaches adsorption saturation, mi is the initial mass of dry foam material, and A is the area of foam material.
[0077] The relationship between the mass of water vapor adsorbed per unit area of Cu3(HHTP)2 foam material and time is shown in Figure 3 .from Figure 3 It can be seen that under different humidity conditions, the Cu3(HHTP)2 foam material can reach adsorption saturation within 20 to 25 minutes, the adsorption rate is fast, and the higher the humidity, the faster the adsorption rate.
[0078] The adsorption time was set to 1 hour under the condition of relative humidity of 15-20%, and 1.5 hours under the condition of relative humidity of 33-99%. The saturated adsorption capacity of Cu3(HHTP)2 foam material under different humidity was tested, and the results are shown in Figure 4 .from Figure 4 It can be seen that the saturated adsorption capacities of Cu3(HHTP)2 foam materials per unit area within the relative humidity range of 15-99% are 1.4, 6.125, 7.2, 7.7, 8.625, 9.225, 9.675, 10.4, 10.775, and 12.425 g / m –2 .
[0079] (4) The Cu3(HHTP)2 foam material prepared in Example 2 was used as a sample, and the reflectivity of the Cu3(HHTP)2 foam material in the full sunlight spectrum was tested using a UV-visible-near infrared spectrophotometer (Shimadzu UV-3600i Plus, Shimadzu, Japan), and its light absorption rate A (%) was calculated according to the following formula:
[0080] A=1-RT
[0081] Wherein, R is reflectivity (%), and T is transmittance (%).
[0082] The absorbance test results are shown in Figure 5 .from Figure 5 It can be seen that the Cu3(HHTP)2 foam material exhibits strong absorption capacity in the entire solar light band. In the wavelength range of 500-1900nm (visible light band and infrared band), its light absorption rate is higher than 80%, and can reach up to 99.5%.
[0083] (5) The Cu3(HHTP)2 foam material prepared in Example 2 was used as a sample. A xenon lamp (CME-SL500, Beijing Zhongke Micro Energy) was used to simulate sunlight in an indoor environment. An infrared thermal imager (TES-132, Taiwan TES Electronics Industry) was used to record the change of the maximum surface temperature of the Cu3(HHTP)2 foam material with time before and after illumination. The results are shown in Table 1. Figure 6 .from Figure 6 It can be seen that the surface temperature of the Cu3(HHTP)2 foam material rises rapidly to 60°C within 10 seconds, and the surface temperature can rise to about 75°C at the highest. After the light is stopped, the surface temperature drops rapidly and drops to 35°C within 20 seconds, which indicates that the surface of the Cu3(HHTP)2 foam material of the present invention has good light-heat conversion ability and thermal conductivity.
[0084] (6) The thermal conductivity of common MOF materials (MOF-303, MOF-801) and Cu3(HHTP)2 powder, as well as the Cu3(HHTP)2 foam material of Example 2, is tested. The test results are shown in Figure 7 .from Figure 7 It can be seen that the thermal conductivity of Cu3(HHTP)2 foam material is higher than that of Cu3(HHTP)2 powder and common MOF materials (MOF-303, MOF-801), indicating that Cu3(HHTP)2 foam material has excellent thermal conductivity.
[0085] (7) The desorption performance of the Cu3(HHTP)2 foam material of Example 2 was tested. When the mass of the Cu3(HHTP)2 foam material was simulated under sunlight in an indoor environment, the relationship between the mass and time of the Cu3(HHTP)2 foam material was investigated to explore the desorption performance of the Cu3(HHTP)2 foam material. The results are shown in Figure 8 .from Figure 8 It can be seen that while the surface temperature of the Cu3(HHTP)2 foam material rises rapidly, the water desorption rate per unit area of the foam material is rapid, with an average desorption rate of 30.6 gm –2 h –1 This indicates that Cu3(HHTP)2 foam material has excellent photothermal properties, which plays an important role in the realization of the solar-driven desorption step in the air water extraction process.
[0086] (8) In order to explore the stability of the Cu3(HHTP)2 foam material during cyclic use, a water adsorption / photothermal desorption cycle test was performed on it. During the test, the Cu3(HHTP)2 foam material of Example 2 was first dried in an oven at 80°C, then taken out and placed directly on a balance for 2 hours of adsorption. During desorption, the xenon lamp light source was turned on and the light power density was set to 1 kW m –2The desorption time was 1 hour and the test process was repeated 15 times. The cyclic stability test of the foam material was carried out in a laboratory environment with an air temperature of 20.0±0.5℃ and a relative humidity of 15±10%. The adsorption and desorption cycle test results of Cu3(HHTP)2 foam material are shown in Fig. 9 During the second cycle, the adsorption capacity of the Cu3(HHTP)2 foam material decreased to a certain extent, and then remained stable. After the eighth cycle, the saturated adsorption capacity of the Cu3(HHTP)2 foam material no longer decreased, indicating that it has strong stability and can be reused in the air water extraction device.
[0087] After 15 cycles, the PXRD results of Cu3(HHTP)2 foam are shown in Fig.10 There is no obvious change in the position and intensity of the diffraction peaks in the spectrum, indicating that the crystallinity of the material is maintained, which can further prove that the Cu3(HHTP)2 foam material has the stability of water vapor adsorption and desorption cycle.
[0088] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention. The techniques, shapes, and structural parts not described in detail in the present invention are all known technologies.
Claims
1. A method for preparing a MOF composite adsorbent based on copper foam, characterized in that: The preparation method comprises the following steps: immersing a copper hydroxide foam block in a HHTP solution, sealing the block and reacting the block at 68 to 75° C. for 2 to 4 hours, washing the obtained solid with deionized water, ethanol and acetone, and drying the solid in a vacuum environment at 70 to 80° C. to obtain a MOF composite adsorbent based on copper foam.
2. The preparation method according to claim 1, characterized in that: The configuration of the HHTP solution is as follows: Add 2,3,6,7,10,11-hexahydroxytriphenylene into dimethylacetamide, disperse by ultrasonic wave, and prepare an organic solution; The organic solution was mixed with deionized water in a volume ratio of 1:10 to obtain a HHTP solution.
3. The preparation method according to claim 2, characterized in that: The concentration of 2,3,6,7,10,11-hexahydroxytriphenylene in the organic solution is 3.5-4 mmol / L.
4. The preparation method according to claim 3, characterized in that: The usage of the copper hydroxide foam block and 2,3,6,7,10,11-hexahydroxytriphenylene is as follows: 0.015-0.025 mol of 2,3,6,7,10,11-hexahydroxytriphenylene is used to soak each cubic centimeter of the copper hydroxide foam block.
5. The preparation method according to claim 1, characterized in that: The preparation of the copper hydroxide foam block is as follows: The pretreated copper foam block is immersed in a mixed alkali aqueous solution and allowed to stand at room temperature for 30 to 60 minutes until the surface of the copper foam block changes from orange to blue, then taken out and repeatedly rinsed with deionized water and ethanol, and vacuum dried to obtain a copper hydroxide foam block; The mixed alkaline aqueous solution contains sodium hydroxide and ammonium persulfate.
6. The preparation method according to claim 5, characterized in that: The concentration of sodium hydroxide in the mixed alkaline solution is 1 mol / L, and the concentration of ammonium persulfate is 0.1 mol / L.
7. The preparation method according to claim 6, characterized in that: Each cubic centimeter of foam copper is soaked in 35 to 45 mL of mixed alkali aqueous solution.
8. The preparation method according to claim 5, characterized in that: The pretreatment of the foam copper block is as follows: Cut the foam copper with a purity of more than 99.9% into cubes, soak them in 10% dilute sulfuric acid for 10 to 15 minutes, soak them in ultrapure water for 20 to 30 minutes, soak them in acetone and ultrasonicate them for 10 to 20 minutes, wash them with deionized water, and dry them.
9. A MOF composite adsorbent based on copper foam, characterized in that: The MOF composite adsorbent is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the MOF composite adsorbent according to claim 9 in adsorption-type air water extraction.
Citation Information
Cited By
Photothermal regenerative atmospheric water capture method and device based on mg3(hhtp)2
CN122669764A
